Diagnostic value of Tei index for acute myocardial infarction in patients presenting to emergency department with ischemic chest pain and correlation with Hs-troponin - ONUR, ÖZGE ECMEL (SAGE PUBLICATIONS LTD, 2019)
Background: Acute myocardial infarction is one of the most common causes of mortality in developed countries, and high-sensitive troponin test usually becomes positive within 3 h from the onset of symptoms. Myocardial perfusion index (Tei index) is a parameter measured during the echocardiographic examination. Objectives: The aim of this study is to investigate the diagnostic value of the Tei index for early diagnosis of acute myocardial infarction in the emergency department and to evaluate the correlation between the Tei index and Hs-Troponin value. Materials and Methods: A total of 129 cases were evaluated, and patients were divided into two groups according to their final diagnosis as acute myocardial infarction (non-ST segment elevation myocardial infarction) and non-acute myocardial infarction groups. Baseline and third-hour Hs-Troponin levels and Tei index values were determined, and their correlation was analyzed. Results: A total of 84 cases were diagnosed with acute myocardial infarction (non-ST segment elevation myocardial infarction), 84.5% had positive Tei index results at the time of admission while the remaining 45 patients were diagnosed as non-acute myocardial infarction and only 48.9% of them had positive Tei index. The diagnostic value of the Tei index and Hs-troponin were calculated as 79.8% and 60%; 67.9% and 60%, respectively. Also, we found that a 0.02 or more increase in the Tei index value has a 97.6 sensitivity and 97.5 specificity for the diagnosis of non-ST segment elevation myocardial infarction. A weak correlation was found between the Tei index and Hs-Troponin values in the acute myocardial infarction group (r = 0.425) and a negative correlation in non-acute myocardial infarction patients at presentation. Conclusion: It is suggested that the use of Tei index might be used as a supportive measure for the early diagnosis of acute myocardial infarction, and the deterioration of Tei index seems to be more significant than Hs-Troponin especially in ruling out acute myocardial infarction.
Keywords: Acute coronary syndrome; myocardial infarction; Tei index; troponin; chest pain; PERFORMANCE INDEX; TISSUE-DOPPLER; HEART-FAILURE